The Impact of the German Minimum Wage on Individual Wages and Monthly Earnings - Patrick Burauel; Marco Caliendo; Markus M. Grabka; Cosima Obst; Malte Preuss; Carsten Schröder; Cortnie Shupe (Jahrbücher für Nationalökonomie und Statistik, 2020)
This paper evaluates the short-run impact of the introduction of a statutory minimum wage in Germany on the hourly wages and monthly earnings of workers targeted by the reform. We first provide detailed descriptive evidence of changes to the wage structure in particular at the bottom of the distribution and distinguish between trends for regularly employed and marginally employed workers. In the causal analysis, we then employ a differential trend adjusted difference-in-differences (DTADD) strategy to identify the extent to which these changes in wages and earnings can be attributed to the minimum wage introduction. We find that the minimum wage introduction can account for hourly wage growth in the order of roughly 6.50.166em% or exteuro0.45/hour and an increase in monthly earnings of 6.60.166em% or exteuro53/month. Despite finding wage growth at the bottom of the distribution, the paper documents widespread non-compliance with the mandated wage floor of exteuro8.50/hour.
Keywords: J31; J38; J22; 330; Minimum wage; Wage and earnings structure; Inequality